Dysfunkcja rozkurczowa lewej komory – praktyczne znaczenie dla anestezjologa - Zawadka, Mateusz; Marchel, Michał; Andruszkiewicz, Paweł (Anestezjologia Intensywna Terapia, 2020)
Bedside point-of-care echocardiography is being increasingly incorporated in perioperative assessment and in intensive care units. Because of availability of tissue Doppler imaging in the modern ultrasound machines there has been an increased interest in research of diastolic function of left ventricle. The diastolic function is crucial for the hemodynamically effective function of the heart. Diastolic dysfunction is a well-established risk factor of the major adverse cardiac events during perioperative period, complications during weaning from ventilator and prognostic factor of mortality in septic shock.